Seasonal distribution of deep groundwater fluoride, geochemical factors and ecological risk for irrigation in the Shendong mining area, China - Hao, Chunming; Wang, Yantang; He, Kaikai; Gui, Herong (Frontiers in Environmental Science, 2022)
High-fluoride (F-) deep groundwater in the vicinity of mining areas poses severe ecological risks. In this study, we aimed to characterize and reveal the seasonal distribution and influencing factors of elevated F- concentrations in the deep groundwater in the Shendong mining area, Shaanxi and Inner Mongolia province, China. In addition, the ecological risks associated with F- concentrations in irrigation water were assessed. During the wet and dry seasons, the F- concentrations in mine water samples ranged between 0.12 and 13.92 mg/L (mean: 4.24 mg/L) and between 0.20 and 17.58 mg/L (mean: 4.59 mg/L), respectively. The F- content of mine water was clearly higher during the dry season than that during the wet season. F- concentrations in deep groundwater exhibited consistent spatial distributions during both the dry and wet seasons, with an evident increase from southeast to northwest. The dissolution and precipitation of F--bearing and calcium minerals, cation exchange, competitive adsorption, evaporation, and anthropogenic activities during both the wet and dry seasons were identified as important factors influencing F- concentrations in deep groundwater. In addition, the ecological assessment revealed that 100% and 88.89% of low-F- deep groundwater samples were suitable for practices during the dry and wet seasons, respectively. In contrast 84.00% and 84.62% of high-F- deep groundwater samples were unsuitable for irrigation practices during the dry and wet seasons, respectively. This research provided useful prevention policies of deep groundwater extraction to mitigate environment problems associated with excessive F- irrigation.